DESAIN PEMBELAJARAN AKIDAH AKHLAK MELALUI PENANAMAN NILAI-NILAI PENDIDIKAN AHLUSSUNNAH WALJAMA’AH DI PONDOK PESANTREN DARUL ULUM - Anwar, Anwar; Wahab, Wahab (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
Faith and moral education is one of the subjects included in the Madrasah curriculum, which in learning the subject explains the values ​​of faith and morals which are fundamental for students so that they can apply it in everyday life. While the values ​​of ahlussunnah waljama’ah are very important to instill in students so that the mindsets possessed by students can be diverse and far from extremism and radicalism. This study analyzes how the Darul Ulum Islamic boarding school instills the values ​​of the ahlussunnah waljamaah faith through the learning of faith and moral education and other religious activities. This research includes field research conducted by observation and interviews. The results of this study include: First, the inculcation of the values ​​of the ahlussunnah wal jamaah creed is based on four concepts, namely: moderate ​​(tawasuth), fair ​​('adlun), balanced ​​(tawazun), and tolerance ​​(tasamuh). Second, instilling the values ​​of faith through religious activities aims to preserve religious activities based on ahlussunnah waljama’ah of Nahdlatul Ulama.